Protein, Fiber and Albumin Content of The Formulation of Snakefish Flour (Channa striata) and Cock Flour (Stenochlaena palustris) in Bingka Cake - Octavia, Tera; Handarsari, Erma; Sulistyaningrum, Hersanti; Sya’di, Yunan Kholifatuddin (Ahmar Metastasis Health Journal, 2024)
A type of food that is ready to consume known as "ready-to-use supplementary food" is strong in macronutrients like fat and protein and is high in energy content. It can be used as a nutritional supplement. Ready-to-use supplementary food is a category of prepared food that is high in macronutrients like protein and fat. One of the ready-to-use supplementary foods is Bingka Cake, which is made with a combination of kelakai flour and snakehead fish flour. Snakehead fish has many benefits as it forms new tissues in the body and also regulates fluid balance in tissues and blood vessels. Meanwhile, kelakai has benefits as a blood booster, anti-diarrhea, increases breast milk, and can treat cancer. This research aimed to examine the effect of bingka cake formulations using processed snakehead and kelakai fish flour on protein content, fiber content, and albumin content. This type of research is experimental using the RAL method. Using the formula by comparing the formulations of snakehead fish flour and kelakai flour at P0 (100:0), P1 (25:10), P2 (50:15), and P3 (75:20), with 6 repetitions. Testing protein levels using Kjedahl, fiber levels using Gravimetry, and albumin levels using Bromocresol Green. Data normality testing utilized Shapiro Wilk and was analyzed using the ANOVA test. One-way ANOVA results and further tests using Duncan and Kruskkal Wallis. The highest protein content test results were in P3 (8.59 ± 4.50). The highest fiber content test results were in P3 (3.54 ± 0.79). The highest albumin level test results were in P2 (17.87 ± 2.53). There was an effect of the formulation of snakehead fish and kelakai flour on protein content, fiber content, and albumin content.